(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, who sent down the Book to His servant and His Prophet, may God bless him and grant him peace, to be an argument and a proof, so he excelled in its composition and perfected its utterance with miracle verses detailed in detail. May Allah’s blessings be upon him, his family and his companions, and peace be upon him.